Oil and Gas Investment Opportunities for Companies in Modern Conditions - Niyazbekova, Sh.U.; Ivanova, O.S.; Suleimenova, B.; Yerzhanova, S.K.; Berstembayeva, R.K. (Studies in Systems, Decision and Control, 2021)
The article discusses the company’s oil and gas investment opportunities. Abroad, venture capital companies provide opportunities for direct investment in the growing oil and gas industry. With extensive experience in developing horizontal oil and natural gas fields, venture capital firms use long-term industry knowledge to provide their partners with high-yield investment opportunities that allow them to diversify their investment portfolios and ensure a stable cash flow while simultaneously getting the right to benefits and significant tax. Venture companies are constantly working to reduce the risks associated with oil and gas projects by partnering with the best operators in the industry. This article discusses the company’s oil and gas investment opportunities. Abroad, venture capital companies provide opportunities for direct investment in the growing oil and gas industry. With extensive experience in developing horizontal oil and natural gas fields, venture capital firms use years of industry knowledge to provide their partners with high-yield investment opportunities that allowthem to diversify their investment portfolios and ensure stable cash flow and simultaneously entitle benefits and significant tax. Venture companies constantly working to reduce the risks associated with oil and gas projects by partnering with the best operators in the industry.
Keywords: financial investments; investment attractiveness; investors assessment mechanism; economic viability